2015
DOI: 10.1111/jgh.12845
|View full text |Cite
|
Sign up to set email alerts
|

SNP rs7770370 in HLADPB1 loci as a major genetic determinant of response to booster hepatitis B vaccination: Results of a genome‐wide association study

Abstract: Our results showed that rs7770370 was the most significant genetic factor of response to HB booster. The rs7770370 and nearby SNPs may also contribute to the long-term immunological memory against HB vaccination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 35 publications
3
16
0
Order By: Relevance
“…The association of DPB1*05:01 with undetectable prebooster anti‐HBs levels was represented, which was in accordance with our study . However, among the 14 significant SNPs for HB vaccine response in other Asian populations, only 6 SNPs were identified as associated factors for anti‐HBs Ab levels in the present GWAS, with 31‐74th place significance rankings (Table ) . It is not surprising to observe concordant or contradictory results among the various study subjects and populations.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The association of DPB1*05:01 with undetectable prebooster anti‐HBs levels was represented, which was in accordance with our study . However, among the 14 significant SNPs for HB vaccine response in other Asian populations, only 6 SNPs were identified as associated factors for anti‐HBs Ab levels in the present GWAS, with 31‐74th place significance rankings (Table ) . It is not surprising to observe concordant or contradictory results among the various study subjects and populations.…”
Section: Discussionsupporting
confidence: 89%
“…These findings facilitated GWASs on the HB vaccine response. Wu et al demonstrated that rs7770370 in HLA‐DPB1 is the most significant genetic factor for a lower risk of nonresponse to booster HB vaccination in Taiwanese adolescents. Two HLA‐DPB1 alleles ( HLA‐DPB1*04:02 and HLA‐DPB1*05:01 ), plus five HLA‐DRB1‐DQB1 haplotypes and the BTNL2 gene, were associated with the HB vaccine response in Japanese individuals according to Nishida's study …”
Section: Introductionmentioning
confidence: 99%
“…For example, candidate and GWAS immunogenetic and phamacogenetic studies have identified polymorphisms in HLA, KIR, MICA, and BTN genes associated with immune responses to pathogens causing disease in humans, such as hepatitis C [16] , Mycobacterium leprae [17] , [18] , human immunodeficiency virus [19] , and measles [20] , [21] , [22] . Similar studies have identified novel genes impacting immune responses to vaccines, including hepatitis B, rubella, influenza A, smallpox, anthrax, and mumps [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] . Our gene association studies of measles-mumps-rubella (MMR) vaccines have demonstrated that inter-individual variations in measles vaccine virus-induced humoral and cellular responses are significantly associated with polymorphisms in immune response genes and, together with HLA alleles, explain ∼30% of the inter-individual variability in humoral response [5] , [34] , [35] , [36] .…”
Section: Rationale and Examples Of Vaccinomics And Adversomicsmentioning
confidence: 73%
“…The third GWAS used subjects with detectable and undetectable (> or < 1 mIU/mL, respectively) post-booster antibody titers from a cohort of booster vaccine recipient Taiwanese adolescents who had not responded to primary vaccination as infants[ 81 ]. Significant associations were mapped to the HLA-DP locus.…”
Section: Gwas For Immune Response To Hepatitis B Vaccinementioning
confidence: 99%
“…The lead SNP rs7770370 was in strong LD with rs9277535. HLA-DPB1 alleles *02:01 , *02:02 , *03:01 , *04:01 and *14:01 (encoding 84GGPM87) were associated with vaccine response, whereas *05:01 and *09:01 (encoding 84DEAV87) were associated with vaccine nonresponse[ 74 , 81 ]. These associations were further confirmed in a Japanese population[ 82 ].…”
Section: Gwas For Immune Response To Hepatitis B Vaccinementioning
confidence: 99%